Experimental study of laser-induced isomerization dynamics of specific C2H2q ions - Jochim, Bethany; Zohrabi, M.; Severt, T.; Berry, Ben; Betsch, K. J.; Feizollah, Peyman; Rajput, Jyoti; Wells, E.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2020)
We investigate intense, ultrafast laser-induced isomerization and two-body fragmentation of acetylene monocations and dications using coincidence three-dimensional momentum imaging. Whereas the vast majority of previous work on strong-field isomerization and fragmentation of acetylene has necessarily involved ionization, by focusing solely on dissociation of ion-beam targets, we ensure that the dynamics ensue within a single molecular ion species, potentially simplifying interpretation. We demonstrate the rich information that can be extracted from such a measurement and discuss advantages and disadvantages of this approach.